(Not) Playing Games: Player-Produced Walkthroughs as Archival Documents of Digital Gameplay - James Newman (International Journal of Digital Curation, 2011)
The subject of digital game preservation is one that has moved up the research agenda in recent years with a number of international projects, such as KEEP and Preserving Virtual Worlds, highlighting and seeking to address the impact of media decay, hardware and software obsolescence through different strategies including code emulation, for instance. Similarly, and reflecting a popular interest in the histories of digital games, exhibitions such as Game On (Barbican, UK) and GameCity (Nottingham, UK) experiment with ways of presenting games to a general audience. This article focuses on the UK’s National Videogame Archive (NVA) which, since its foundation in 2008, has developed approaches that both dovetail with and critique existing strategies to game preservation, exhibition and display.